Applied Magnetic Resonance - Salikhov, Kev M.; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer.)
Applied Magnetic Resonance provides an international forum for the application of magnetic resonance in physics, chemistry, biology, medicine, geochemistry, ecology, engineering, and related fields. Applied Magnetic Resonance publishes original articles with a strong emphasis on new applications of the technique and on new experimental methods. Routine applications are outside the scope of the journal. Review articles are invited on methods and applications of NMR, NQR, EPR, Moessbauer spectroscopy, etc. Special issues are put together on single topics. Separate sections are provided for book reviews and Letters to the Editor. Fields of interest: Chemical physics, analytical chemistry, chemical kinetics, structure determination and spectroscopy, medical physics.
Keywords: Spectroscopy; Organic chemistry; Physical chemistry; Atoms; Physics; Matter; Solid state physics; Solid State Physics; Spectroscopy/Spectrometry.; Atoms and Molecules in Strong Fields, Laser Matter Interaction; Physical Chemistry; Organic Chemistry